Evaluation of the California Mental Health Services Authority's Prevention and Early Intervention Initiatives Progress and Preliminary Findings - Burnam, M. Audrey (RAND Corporation, 2014)
Evaluates the progress of the California Mental Health Services Authority's statewide Prevention and Early Intervention initiatives and establishes a baseline for risk factors and long-term outcomes that the initiatives target.